2019
DOI: 10.1136/annrheumdis-2018-214725
|View full text |Cite|
|
Sign up to set email alerts
|

Sequencing of the MHC region definesHLA-DQA1as the major genetic risk for seropositive rheumatoid arthritis in Han Chinese population

Abstract: ObjectiveThe strong genetic contribution of the major histocompatibility complex (MHC) region to rheumatoid arthritis (RA) has been generally attributed to human leukocyte antigen (HLA)-DRB1. However, due to the high polymorphisms and linkage disequilibrium within MHC, it is difficult to define novel and/or independent genetic risks using conventional HLA genotyping or chip-based microarray technology. This study aimed to identify novel RA risk variants by performing deep sequencing for MHC.MethodsWe first con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 54 publications
(76 reference statements)
0
28
1
Order By: Relevance
“…Another recent study applied deep sequencing in order to identify novel genetic risks and identified two novel factors. One of them, that is, HLA‐DQα1:160 D, conferred strong susceptibility to ACPA‐positive RA and another one, HLA‐DRβ1:37N appeared to be protective . By using computational modeling, the authors suggested a possible role of these factors in antigen recognition by respective HLA‐typed T cells and their subsequent activation.…”
Section: Hypotheses Elucidating Mechanisms Of Autoimmunity In Ramentioning
confidence: 99%
“…Another recent study applied deep sequencing in order to identify novel genetic risks and identified two novel factors. One of them, that is, HLA‐DQα1:160 D, conferred strong susceptibility to ACPA‐positive RA and another one, HLA‐DRβ1:37N appeared to be protective . By using computational modeling, the authors suggested a possible role of these factors in antigen recognition by respective HLA‐typed T cells and their subsequent activation.…”
Section: Hypotheses Elucidating Mechanisms Of Autoimmunity In Ramentioning
confidence: 99%
“…The GAsP reference panel showed higher imputation accuracy (93%-95%) compared with 1000 Genome Asian panel (<90%). 30 Four SNPs within known GWAS associations with RA were included: rs9268839 (HLA-DRB9), 31 32 rs9275376 (HLA-DQB1), [33][34][35][36] rs4947332 (tag-SNP for HLA-DRB1*04:07) and rs7752903 (TNFAIP3). 31 32 In addition, a panel of five ancestry informative markers (negative control) were selected to estimate the potential effects of population stratification: rs174583 (11q12.2), rs11745587 (5q31.1), rs521188 (1p31.3) and rs7740161 (6q23.2).…”
Section: Dna Extraction Snp Selection and Genotypingmentioning
confidence: 99%
“…We read with great interest the paper by Guo et al 1 addressing the HLA association with seropositive rheumatoid arthritis (RA) in Han Chinese. The authors reported that aspartic acid at position 160 of HLA-DQα1 (HLA-DQα1:160D) was the major risk factor.…”
mentioning
confidence: 99%